Decadência do crédito tributário e sua atual disciplina no direito brasileiro - Hayashi, Marisa Regina Maiochi (2013)
This research aims to study extensively the decay of the tax credit and its current course in Brazilian law. To achieve this goal, in this dissertation law is addressed from a communicational aspect and the logic semantic constructivism method is applied. In the cycle of law positivation, we expose the way in which the rules of decay only take effect after applied, because the flow of time does not operate alone the effect of rights extinction. It always takes a human act of application of the law that aims extinctive facts and their respective effects on individual and concrete decay rules. With an emphasis on normative level, we seek to identify in the general and abstract rules the criteria to determine the time and duration of the initial limitation period, identifying the relevant legal rules and considering even the chance of interruption of decay period. Despite scientific research and case law on the subject-matter, the decay of the tax credit is yet a controversial issue, what justifies a large study